Criminal Provisions Against Foreign Fishermen Who Carry Out Fishing In The Exclusive Economic Zone (Study Decision No: 5/Pid.sus.PRK/2019/PN.Mdn) - Rointan Br. Manullang (CERED Indonesia Institute, 2023)
This type of research is normative legal research. In this research, library materials, legal research, judges' decisions and laws are the basis for which research is classified as secondary data. The nature of this research is descriptive analytical research that uses primary and secondary legal materials. , and tertiary. Criminal provisions against foreign fishermen who carry out fishing or illegal fishing in fisheries management areas, especially in the Indonesian Exclusive Economic Zone, which often occurs. The perpetrators of this crime are foreign fishermen. Law enforcement and criminal responsibility given to perpetrators of criminal acts in the Indonesian Exclusive Economic Zone are very weak, which only provides criminal sanctions for fines, which do not provide a deterrent effect on other foreign fishermen. And the actions of foreign fishermen can damage the marine ecosystem by using foreign fishermen using trawl fishing gear, which is prohibited by law. Law enforcement must use other efforts so that accountability and criminal provisions against foreign fishermen who catch fish in fisheries management areas, especially in the Indonesian Exclusive Economic Zone must make other efforts to reduce foreign actors or fishermen who enter the Indonesian fisheries management area, especially the Economic Zone Exclusively for Indonesia which does not have SIPI or SIUP. By increasing human resources, improving facilities and infrastructure in registering foreign ships entering the Indonesian Exclusive Economic Zone. By increasing security operations in a strict, routine and organized manner.